Adequate housing habitability: analysis of the types of apartments in the Júlio Prestes Complex, ambiance of the historic center of São Paulo - Vieira, Renata Zucoloto; Jesus, Thamiris Ramalho de; Salcedo, Rosio Fernández Baca (Technical and Scientific Journal Green Cities, 2024)
The housing deficit in the city of São Paulo reaches 27.21% of the Brazilian territory (SEADE, 2022). To reduce the rate, it depends on government planning focused on social housing policies, which must meet the principles of adequate housing and sustainability. The Júlio Prestes Complex, belonging to the Public-Private Housing Partnership Program, located in the historic center of São Paulo, houses social and popular market housing for families with income between RF1 and RF6, distributed over 2 blocks. Therefore, the objective is to analyze whether the types of apartments in towers 1 to 4 of Block 49 of the Júlio Prestes Complex meet the habitability parameter of adequate housing. Methodology: the habitability analysis was carried out according to the criteria of capacity, types of housing, materiality, conservation, thermal and lighting comfort, based on the parameters of Boueri (2004), the program notice (2014) and the project delivered by construction company. In this way, the study falls within the theme of built environment and sustainability, which is very relevant as it involves a pre- and post-occupancy assessment with a focus on housing quality and sustainable development. Results: The habitability parameter of adequate housing in the Júlio Prestes Complex is partially met, as it complies with the guidelines of the notice, however all areas of the rooms, except the living room and double bedroom, are precarious. Contributing to an in-depth analysis of the habitability of adequate housing, the article covers physical, social and environmental aspects, as it cross-references data proposed by policy, authors and national standards.
Keywords: Júlio Prestes Complex; Habitability; Adequate housing